Hermit crabs (Crustacea: Decapoda: Anomura) inhabiting the intertidal and shallow subtidal region of Red Sea coast of Egypt - El-Wakeil, Khaleid F. Abd; Ahmed, Elham S.; Obuid-Allah, Ahmad H.; El-Shimy, Nasser A. (Zootaxa, 2009)
The present work surveys hermit crab species inhabiting the intertidal and shallow subtidal region in the Red Sea coast of Egypt, and presents an identification key for surveyed hermit crabs. Twelve hermit crab species were recorded from the 29 sites along the Red Sea coast of Egypt. These species belong to three families (Coenobitidae, Paguridae and Diogenidae) and seven genera. The dominant species in this survey were Clibanarius signatus and Calcinus latens. The less dominant species in this survey were Diogenes pallescens, D. costatus, D. lagopodes and Clibanarius carnifex and rarer species were Dardanus woodmasoni, Diogenes tirmiziae, Coenobita scaevola, Clibanarius longitarsus, Cestopagurus coutieri and Pagurus cavicarpus. Identification key for the recorded hermit crabs species is provided.